Biology 1 (bio0415) workbook - Mohd Nasohah, Nor Sa'adah; Ng, Muhammad Ng Chee Hong; Zahari, Shafiyyah Solehah; Muslim, Rozita; Ghazali, Zahala; Abdul Aziz, Nurul Azrina; Abdullah, Azyril Iskandar; Abdullah Sani, Siti Hajar; Teruk, Kamaril Azlah; Hamzah, Haliza; Mohd Sharuddin, Norfazlina (IIUM PRESS, 2020)
Biology I (Bio415) Workbook for BIO0415 course. This book is specially written for foundation students taking Biology at Centre for Foundation Studies, IIUM. The purpose of this workbook is to provide students with exercises to help them understand topics in Biology This Biology I Workbook consists of multiple-choice questions and structure questions for 14 chapters. Answer schemes and feedbacks are provided at the end of each chapter as guidance for the students to understand the concepts. The questions in each chapter were tested on students and moderated to confirm the validity.